EFFECT OF PRESSING PRESSURE ON INDICES OF FIBREBOARDS MANUFACTURED FROM WOOD OF HARD BROAD-LEAVED SPECIES - Mihajlova, Julia; Savov, Viktor (Innovation in Woodworking Industry and Engineering design, 2013)
The main factor defining the performance of the hard thin FBs is the pressure applied in the process of piezothermal treatment. In order to manufacture a product designed by engineering, the pressing pressure should be with a specific value determined in advance. The latter is in correlation dependence on the tree species, the characteristics of the wood-fibre mass and of the wood-fibre carpet. Determining, out of these factors, is the resistance that the carpet shows un der the applied external load, with it depending mainly on the characteristics of the mass and, to a determining degree, on the tree species used for the manufacture of the boards. In this paper, an investigation on the effect of pressure during manufacture of thin FBs on the basis of beech and cerris oak wood is presented. Derived are the main dependences of the performance of FBs on the factors examined in case of application of the methods of regression analysis, with use of the least squares method. Established are the optimum values of pressure depending on the thickness of the boards and the design thickness set.